Renal denervation restores autonomic imbalance and prevents atrial fibrillation in patients with hypertensive heart disease : a pilot study - Heradien, Marshall Jacobus (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.